Radioprotective Role in Lung of the Flaxseed Lignan Complex Enriched in the Phenolic Secoisolariciresinol Diglucoside (SDG) - Christofidou-Solomidou, Melpo (2012)
While dietary wholegrain Flaxseed (FS) has potent anti-inflammatory, anti-fibrotic and antioxidant properties in murine models of acute and chronic lung injury, the main bioactive ingredient that contributes to these protective effects remains unknown. This study evaluated the lignan complex of FS (FLC) enriched in secoisolariciresinol diglucoside with respect to lung radioprotective and tumor radiosensitizing efficacy using a mouse model of thoracic radiation-induced pneumonopathy. C57/Bl6 mice were fed 0% FS, 10% FS, 10% FLC or 20% FLC for 3 weeks, then irradiated with a single fraction (13.5 Gy) of X-ray radiation treatment (XRT). Mouse survival was monitored for 4 months after irradiation and inflammatory lung parameters were evaluated in bronchoalveolar lavage (BAL) fluid. Gene and protein levels of protective antioxidant and phase II enzymes were evaluated in lung tissue using qPCR and protein levels were verified by immunoblotting. Prolonged administration of the FLC diet was well tolerated and was not associated with any toxicity. Importantly, comparable to the whole grain 10% FS diet, irradiated mice fed 10% and 20% FLC diets displayed improved survival. Improved hemodynamic measurements were also recorded in irradiated mice fed 10% FS or 10% FLC diet compared to irradiated 0% FS fed mice. Flaxseed lignan complex diet also attenuated polymorphonuclear infiltration and overall lung inflammation to levels comparable to those in nonirradiated mice. Flaxseed lignan complex, similarly to FS, up-regulated gene expression as well as protein levels of protective antioxidant enzymes such as heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase 1 (NQO1). Dietary FLC induced radiosensitizing effects in our murine model of metastatic lung cancer. Importantly, protection of normal tissue does not thwart tumor cell death by radiation treatment. The dietary lignan complex of FS, mainly consisting of the phenolic secoisolariciresinol, is protective against radiation pneumonopathy in vivo while not hindering the tumoricidal effects of radiotherapy.